The anesthetic approach to repeated cesarean sections: A prospective cohort study - Jacob Weinstein; Rasha Muhalwes; Alexander Ronenson; Stephen H. Halpern; Sorina Grisaru-Granovsky; Tamer Akawi; Yaacov Gozal; Daniel Shatalin; Alexander Ioscovich (Elsevier, 2024)
Objective: Each repeat cesarean section (CS) potentially adds surgical complexity. The determination of appropriate anesthesia strategy to meet the surgical challenge is of crucial importance for the maternal and neonatal outcome. Study design: This prospective cohort study was conducted from 1-Jan-2021 to 31-Dec-2021 at a single large obstetric centre of all repeat CS. We compared the characteristics and the appropriateness of the anesthesia techniques for low-order repeat CS (LOR-CS) (1 or 2 previous CS) and high order repat CS (HOR-CS) group (3 or more repeat CS). Results: During the study period, 1057 parturients met the study entry criteria, with 821 parturients in the LOR-CS group and 236 parturients in the HOR-CS group. The use of spinal anesthesia was more common for HOR-CS 84.3%. Overall surgical time varied between LOR-CS (38 min, 29-49) and HOR-CS (42 min, 31-57) (p = 0.004).The rate of moderate and severe adhesions was relatively high in HOR-CS and the duration of overall surgical time for cases with mild adhesions was 38 min (29-48), for moderate adhesions was 44 min (34.8-56.5), and for severe adhesions was 56 min (44.8-74.3). There was no significant difference in the Estimated Blood Loss (EBL) between LOR-CS and HOR-CS, with values of 653 ± 292 ml vs. 660 ± 285 ml, respectively. Conclusion: Our data indicate that spinal anesthesia, standard monitoring and regular anesthetic setup are safe and suitable for the majority of HOR-CS, except in cases with high suspicion of placental accreta spectrum.